2021
DOI: 10.1016/j.eneco.2021.105177
|View full text |Cite
|
Sign up to set email alerts
|

Network utilities performance and institutional quality: Evidence from the Italian electricity sector

Abstract: It is generally accepted that institutions are important for economic development. However, whether the performance of regulated utilities within a country is affected by the quality of institutions is yet to be investigated thoroughly. We analyse how the quality of regional institutions impact performance of Italian electricity distribution utilities. We use a stochastic frontier analysis approach to estimate cost functions and examine the performance of 108 electricity distribution utilities from 2011 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Bastianin et al (2018) surveyed the literature on regulatory reform, but they did not cover the utility sector. Borghi et al (2016), Soroush et al (2021), andCastelnovo et al (2019) found that electricity and telecom firms can improve their performance through better quality of governance, but they did not study the effects of product market regulations.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Bastianin et al (2018) surveyed the literature on regulatory reform, but they did not cover the utility sector. Borghi et al (2016), Soroush et al (2021), andCastelnovo et al (2019) found that electricity and telecom firms can improve their performance through better quality of governance, but they did not study the effects of product market regulations.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…The Portuguese electricity sector stepped into its final stage of market liberalization in 2006 (Amorim et al, 2013). Previous studies suggest that electricity market reforms could improve efficiency (Barros, 2008;Ma and Zhao, 2015;Lundin, 2020;Bobde and Tanaka, 2020) but in some cases this job may not be perfectly done as the reforms are hampered by incomplete deregulation and practical factors (Sun and Wu, 2020;Lee et al, 2021;Mirza et al, 2021). On the other hand, previous studies on technical efficiency in the electricity sector mostly focus on one of the subsectors and the impact of operational factors on efficiency has been less discussed compared to environmental factors (Growitsch et al, 2012;Karim and Pollitt, 2017;Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by previous evidence, incomplete deregulation in the electricity sector may hinder efficiency improvement (Sun and Wu, 2020). The Portuguese electricity market is far from competitive as state guaranteed prices and feed-in tariffs still dominate the market (Amorim et al, 2013).…”
Section: General Commentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, several studies on quality management have been conducted in the electricity sector [23][24][25]. The country's electricity sector is important and related to people.…”
Section: Introductionmentioning
confidence: 99%